WAYANG JAWA SEBAGAI PEREKAT SOSIAL: HARMONI MUSLIM-KATOLIK DI DESA KOLAM - Fiqih Faras Syahara; Irwansyah Irwansyah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
Diverse beliefs in society often pose a challenge to social stability if not managed through inclusive cultural means. This study aims to analyze the role of Javanese Wayang art as a social glue that constructs harmony between Muslims and Catholics in Kolam Village. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews with village religious authority staff, cultural practitioners who understand the philosophy of wayang, and residents actively involved in interfaith interactions, and documentation collecting photo archives of activities, and relevant literature to support the validity of the findings. The analysis was conducted using the Miles & Huberman interactive model through the stages of reduction, presentation, and drawing conclusions. The results show that Javanese Wayang functions as a